PENGARUH METODE PEMBELAJARAN DAN MOTIVASI BELAJAR TERHADAP KETERAMPILAN TEKNIK DASAR PERMAINAN BOLAVOLI SISWA SMA N 1 SILAUT - Muhammad Hidayat Z (Ensiklopedia of Journal, 2019)
Based on direct observation that had conducted it could be seen that boy students were not be able to do basic volleyball good technique. In addition, learning method that was given by teacher delivered as classical and individual. This research aims to see the difference of divergent discovery learning method, conventional learning and motivation to study for students toward basic volleyball technique. The type of this research is a quasi experimental, population from this research is all boy students of SMA N 1 Silaut amount of 184 students, where as the sample is 75 students, the number of sample became 40 students after it was divided into groups (75x27%=20) for high motivation to study and (75x27%=20) for low motivation to study. The instrumental from this research used such as volleying test, passing test and serving test. The data that received was analyzed with two-way Anova and continued with Tuckey Test. The result from the data analysis showed that: (1) Over all there is a difference of the result volleyball learning method between divergent discovery groups and the conventional, (2) there is an interaction between learning method and motivation to study, (3) At high motivation learning category, the result of basic volleyball techniques from the group student who was given divergent discovery learning method is much effective than conventional learning groups, (4) At low motivation category, basic volleyball techniques from the group student who was taught conventional learning method is effective than the group of divergent discovery.